Microvascular Dysfunction in Skeletal Muscle Precedes Myocardial Vascular Changes in Diabetic Cardiomyopathy: Sex-Dependent Differences - Loai, Sadi; Sun, Xuetao; Husain, Mansoor; Laflamme, Michael A.; Yeger, Herman; Nunes, Sara S.; Cheng, Hai-Ling Margaret (Frontiers in Cardiovascular Medicine, 2022)
Aim: To uncover sex-related microvascular abnormalities that underlie the early presentation of reduced perfusion in leg skeletal muscle but not in heart muscle in a type II rat model of diabetic cardiomyopathy. Methods/Results: Diabetes was induced using a non-obese, diet-based, low-dose streptozotocin model in adult female (18 diabetic, 9 control) and male rats (29 diabetic, 11 control). Time-course monitoring over 12 months following induction was performed using echocardiography, treadmill exercise, photoacoustic imaging, flow-mediated dilation (FMD), histopathology, and immunohistochemistry. Diabetic rats maintained normal weights. Hypertension appeared late in both diabetic males (7 months) and females (10 months), while only diabetic males had elevated cholesterol (7 months). On echocardiography, all diabetic animals maintained normal ejection fraction and exhibited diastolic dysfunction, mild systolic dysfunction, and slightly enlarged left ventricles. Exercise tolerance declined progressively and early in males (4 months), later in females (8 months); FMD showed lower baseline femoral arterial flow but unchanged reactivity in both sexes (5 months); photoacoustic imaging showed lower tissue oxygen saturation in the legs of diabetic males (4 months) and diabetic females (10 months). Myocardial perfusion was normal in both sexes. Histopathology at the final timepoint of Month 10 (males) and Month 12 (females) revealed normal myocardial microvasculature in both density and structure, thus explaining normal perfusion on imaging. However, leg muscle microvasculature exhibited perivascular smooth muscle thickening around small arterioles in diabetic females and around large arterioles in diabetic males, explaining the depressed readings on photoacoustic and FMD. Histology also confirmed the absence of commonly reported HFpEF markers, including microvessel rarefaction, myocardial fibrosis, and left ventricular hypertrophy. Conclusion: Exercise intolerance manifesting early in the progression of diabetic cardiomyopathy can be attributed to decreased perfusion to the leg skeletal muscle due to perivascular smooth muscle thickening around small arterioles in females and large arterioles in males. This microvascular abnormality was absent in the myocardium, where perfusion levels remained normal throughout the study. We conclude that although skeletal muscle microvascular dysfunction of the vasculature presents at different levels depending on sex, it consistently presents early in both sexes prior to overt cardiac changes such as rarefaction, fibrosis, or hypertrophy.